Pré-compreensão e linguagem: horizontes hermenêuticos da decisão judicial - Valéria Cássia Dell'Isola (2019)
The title of the thesis presented, namely "Pre-comprehension and language: hermeneutical horizons of judicial decision" reveals the nucleus to be worked, as well as points to the irradiations of the hermeneutical reflections that the development of the thematic can lead. In order to do so, one must understand the jurisdictional rendering, especially the act of judicial decision, phenomenologically and epistemologically, on these two inseparable pillars: language and pre-comprehension. The study of language is based on the Heideggerian premise that language is the privileged locus of understanding and that it constitutes the home of Being. The phenomenology of language, in this respect, reveals itself not only as an instrument of communication between the interlocutors, but as the only way to achieve justice and correct misunderstanding in the judicial sphere. Besides Husserl and Heidegger, it is necessary to bring to the fore other authors of Hermeneutics and Phenomenology. In philosophical analysis, the eristic and the dialectic are equally important for the field of discourse and, to this end, starts from the idea of Socratic maieutics, so that the judicial context is an adequate instrument for solving the lids together with the parties. In this connection, the dialogue with all those involved in the judicial process must take place in an appropriate manner, without there being any silencing due to possible distortions of language that may be devoid of hospitality and otherness. Regarding pre- comprehension, the importance of comparing the legal study with neuroscience must be emphasized. This is because, based on the assumption that the human being is not a blank slate and that, given human vicissitudes, it is not necessary to speak about the neutrality of the individual, it is fundamental to reflect on the phenomena of conformity, authority, anchoring and of hierarchical obedience. Therefore, several researches carried out in foreign universities were brought in this work for reflection in the legal context, mainly in the way in which such phenomena can influence the judicial decision. Neuroscience, therefore, provides the data to be analyzed and, from the perspective of the Phenomenology, it is possible to establish a relation with the intrinsic causes that fall on the decisions of the magistrates. Through this bridge an accurate reflection on authenticity can be made, so that it is clear that it is possible to trace the impartiality of the judges, but it is not possible to demand neutrality. Through this motto, the hermeneutical views of the judicial decision under these two pillars (pre-comprehension and language) are unfolded in this thesis, taking into account the interpretation, the grounds of the decision in the Democratic State of Law, the risks of judicial activism and, above all, ethics and justice in legal discourse.